Characterizing Ischaemic Tolerance in Rat Pheochromocytoma (PC12) Cells and Primary Rat Neurons. (15th January 2021) - Singh, Ayesha; Chow, Oliver; Jenkins, Stuart; Zhu, Lingling; Rose, Emily; Astbury, Katherine; Chen, Ruoli
Highlights: Preconditioning with oxygen and glucose deprivation (OGD) induced ischaemic tolerance in PC12 cells and primary rat neurons. Preconditioning with glucose deprivation (GD) was protective in PC12 cells but not primary rat neurons. Glucose concentration in preconditioning is inversely related to the level of protection conferred in PC12 cells. HIF1 stabilization and it's downstream gene upregulation are associated with OGD- (but not GD-) induced ischaemic tolerance. Abstract: Preconditioning tissue with sublethal ischaemia or hypoxia can confer tolerance (protection) against subsequent ischaemic challenge. In vitro ischaemic preconditioning (IPC) is typically achieved through oxygen glucose deprivation (OGD), whereas hypoxic preconditioning (HPC) involves oxygen deprivation (OD) alone. Here, we report the effects of preconditioning of OGD, OD or glucose deprivation (GD) in ischaemic tolerance models with PC12 cells and primary rat neurons. PC12 cells preconditioned (4 h) with GD or OGD, but not OD, prior to reperfusion (24 h) then ischaemic challenge (OGD 6 h), showed greater mitochondrial activity, reduced cytotoxicity and decreased apoptosis, compared to sham preconditioned PC12 cells. Furthermore, 4 h preconditioning with reduced glucose (0.565 g/L, reduced from 4.5 g/L) conferred protective effects, but not for higher concentrations (1.125 or 2.25 g/L). Preconditioning (4 h) with OGD, but not OD or GD, induced stabilization of hypoxia inducible factor 1α (HIF1α) and upregulation of HIF1 downstream genes ( Vegf, Glut1, Pfkfb3 and Ldha ). In primary rat neurons, only OGD preconditioning (4 h) conferred neuroprotection. OGD preconditioning (4 h) induced stabilization of HIF1α and upregulation of HIF1 downstream genes ( Vegf, Phd2 and Bnip3 ). In conclusion, OGD preconditioning (4 h) followed by 24 h reperfusion induced ischaemic tolerance (against OGD, 6 h) in both PC12 cells and primary rat neurons. The OGD preconditioning protection is associated with HIF1α stabilization and upregulation of HIF1 downstream gene expression. GD preconditioning (4 h) leads to protection in PC12 cells, but not in neurons. This GD preconditioning-induced protection was not associated with HIF1α stabilization.